2017
DOI: 10.1007/s00256-017-2656-z
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound evaluation of the ulnar collateral ligament of the elbow: Which method is most reproducible?

Abstract: US assessment of UCL thickness by all three measurement techniques are reproducible. The JW technique had less interobserver agreement when compared to the Nazarian method, whereas the modified JW technique had greater reproducibility compared to the JW technique and similar to the Nazarian technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
1
4
1
Order By: Relevance
“…Our study also showed that greater pitching elbow UCL thickness (3.4 15,24 although all studies reported a trend toward thicker UCLs in D arms.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Our study also showed that greater pitching elbow UCL thickness (3.4 15,24 although all studies reported a trend toward thicker UCLs in D arms.…”
Section: Discussionsupporting
confidence: 64%
“…Nazarian et al 15 reported mean thickness of 6.3 mm in D arms versus 5.3 mm in ND arms and Ciccotti et al 4 reported measurements of 6.15 mm in D arms versus 4.82 mm in ND arms. Although our absolute measurements were smaller, Popovic et al 20 reported mean UCL thickness of 1.68 mm in D arms and 1.21 mm in ND arms, showing that some discrepancy can be explained by different measurement techniques, 15 , 24 although all studies reported a trend toward thicker UCLs in D arms.…”
Section: Discussioncontrasting
confidence: 56%
“… 18 , 19 , 25 The Modified Jacobson–Ward technique was used to measure the UCL. 31 Parallel cortices were used for measuring UHJS, with particular attention to omitting bone spurs.…”
Section: Methodsmentioning
confidence: 99%
“…Each image was evaluated for UCL thickness and medial UHJS distance in stressed and non-stressed examinations. UCL thickness was measured by the modified Jacobson-Ward technique, 23 whereas UHJS was measured without including bone spurs and from the superior portion of the joint with the cortices parallel. Continuous outcome measures consisted of UCL thickness and area, unloaded UHJS, loaded UHJS, and shoulder ROM measurements.…”
Section: Methodsmentioning
confidence: 99%